Ministry of Tourism and Antiquities Decree No. 295 of the Year 2021 issued on 11/22/2021 = وزارة السياحة والآثار قرار رقم 295 لسنة 2021 صادر بتاريخ 22/11/2021 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic